Crashworthiness analysis and multi-objective optimization for honeycomb structures under oblique impact loading. Issue 4 (15th July 2022) - Ma, Fangwu; Liang, Hongyu; Pu, Yongfeng; Wang, Qiang; Zhao, Ying
Abstract: Oblique impact loading conditions are unavoidable in practical applications, which strongly influence the performance response of energy-absorbing structures. In this paper, the finite element models of four typical cellular structures (hexagon honeycomb, re-entrant hexagon honeycomb, star-shape honeycomb, double arrow honeycomb) are established and experimentally validated. The dynamic responses of four structures under different impact angles (from 0 to 30°) and impact velocities (from 5 to 50 m/s) are investigated. On this basis, the influences of impact angle and impact velocity on the specific energy absorption ( SEA ) and peak crushing force ( PCF ) of four structures are discussed. The results reveal that the negative Poisson's ratio structure has the advantage of energy absorption under axial impact due to the characteristics of compression and contraction at the low impact velocity. The hexagonal honeycomb structure has great advantages in terms of comprehensive energy absorption capacity and better stability at varying inclination angles. The Non-dominated Sorting Genetic Algorithm (NSGA-II) coupled with the ideal point method (IPM) is utilised to explore the optimal design of hexagon honeycomb structure, which is then verified by a detailed crashworthiness comparison with the original design. The optimal honeycomb structure shows excellent crashworthiness characteristics and demonstrates great potential for applications in impact engineering, especially the oblique impact loading situations.